A novel thiol-labile cysteine protecting group for peptide synthesis based on a pyridazinedione (PD) scaffold. Issue 5 (8th November 2021) - Spears, Richard J.; McMahon, Clíona; Shamsabadi, Monika; Bahou, Calise; Thanasi, Ioanna A.; Rochet, Léa N. C.; Forte, Nafsika; Thoreau, Fabien; Baker, James R.; Chudasama, Vijay
Abstract : Herein we establish the compatibility of pyridazinediones (PDs) as thiol-labile cysteine protecting groups in solid phase peptide synthesis (SPPS). Abstract : Herein we report a thiol-labile cysteine protecting group based on an unsaturated pyridazinedione (PD) scaffold. We establish compatibility of the PD in conventional solid phase peptide synthesis (SPPS), showcasing this in the on-resin synthesis of biologically relevant oxytocin. Furthermore, we establish the applicability of the PD protecting group towards both microwave-assisted SPPS and native chemical ligation (NCL) in a model system.